Business Process Reengineering Of Funding On Indonesia’s Islamic Banks - Nur Widigdo, Aslam Mei; Marimin, Marimin; Fahmi, Idqan; Beik, Irfan Syauqi (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2016)
This research attempts to analyze the value chain of Islamic banking business processes and to develop a business processes model on depositors’ funds in order to improve the performance of Islamic banks. Four models of Islamic banking operating in Indonesia are used as the objects of the study. This research applies qualitative study (exploratory) approach and utilizes primary data obtained from questionnaire and interviews. This data are then processed by value stream mapping and process activity mapping. This study shows that the waiting time for services is the sub-stage of business process that does not have value added and categorized as pure waste based on VSM criteria.The reengineering of business process of the third party fundraising may reduce collection time up to 1490 minutes for corporate customer and 22 minutes for individual customer.DOI: 10.15408/aiq.v8i1.2506